Novel method for evaluating the indication for endoscopic papillectomy in patients with ampullary adenocarcinoma - Yamamoto, Kenjiro (Sci Rep, 2021)
This study aimed to determine the clinicopathological features of the subtypes of ampullary carcinoma (AC) to explore the indications for endoscopic papillectomy (EP) in early AC. Fifty-seven patients with AC who underwent curative resection were retrospectively reviewed. The 0/IA stages were significantly more common in the intestinal type (I-type) than in the mixed and pancreatobiliary type (M&PB-type) (90.7% vs 35.7%, P < 0.001). Tis/T1a tumors limited to the ampulla [Tis/T1a(ampulla)] were significantly more likely to be I-type than M&PB-type (74.4% vs 14.3%, P = 0.002). The tub1 rate was significantly higher in the I-type than in the M&PB-type (81.4% vs 35.7%, P = 0.001). In the I-type, the tub1 rate was significantly higher for Tis/T1a(ampulla) than for T1a tumors limited to the sphincter of Oddi (100% vs 42.9%, P = 0.004). These observations suggest that I-type AC with tub1 is an indication for EP. The concordance rate of pathological subtypes between endoscopic biopsy and resected specimens was high (κ = 0.8053, P < 0.001). Tis/T1a(ampulla) showed no lymphovascular or perineural invasion. An endoscopic imaging finding of early AC with I-type and tub1 on biopsy could be an indication for EP. Identifying the pathological subtype of AC by endoscopic biopsy could be a novel preoperative approach for evaluating the indications for EP.